2019
DOI: 10.1016/j.cub.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-Based Ordering of Sequential Actions during Drosophila Courtship

Abstract: Graphical AbstractHighlights d A descending neuron, aSP22, controls multiple actions in Drosophila male courtship d aSP22 activation triggers these actions in the same sequence as found in courtship d The courtship actions are sequenced by a ramp-to-threshold mechanism d Distinct action thresholds are best explained by spike count, not spike frequency SUMMARY Goal-directed animal behaviors are typically composed of sequences of motor actions whose order and timing are critical for a successful outcome. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 41 publications
5
54
0
Order By: Relevance
“…This represents an increase of 70% for all song and 110% for song transitions over a GLM. While we have here accounted for much of the variability in song patterning, we speculate that the remaining variability is due to either some noise in our segmentation of song [3] or the fact that we do not measure some male behaviors that are known to be part of the courtship interaction, including tapping of the female via the forelegs and proboscis extension [49, 72]. The use of new methods that estimate the full pose of each fly [52] combined with acoustic recordings should address this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…This represents an increase of 70% for all song and 110% for song transitions over a GLM. While we have here accounted for much of the variability in song patterning, we speculate that the remaining variability is due to either some noise in our segmentation of song [3] or the fact that we do not measure some male behaviors that are known to be part of the courtship interaction, including tapping of the female via the forelegs and proboscis extension [49, 72]. The use of new methods that estimate the full pose of each fly [52] combined with acoustic recordings should address this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…We find that a pharmacologically relevant blood alcohol concentration (BAC) promotes male aggression. Furthermore, this alcohol dosage impairs male courtship-a goal-directed behavior (4). In addition, there exists a secondary mechanism through which alcohol induces aggression.…”
Section: Main Textmentioning
confidence: 99%
“…This study also identified P1 and a pair of descending neurons named pIP10, likely a member of P2b, as neurons that can initiate male courtship singing ( Figure 1B). Other studies identified the dsx-positive pC2l cluster [35] and the fru-positive aSP22 descending neurons [36] as neurons activating licking and attempted copulation, two later-phase components of mating behavior, in addition to following pursuits and singing.…”
Section: Circuit Basis For Courtship Behavior In D Melanogastermentioning
confidence: 99%